الإبداع وثقافة التغريب فى النص الأدبى الحديث - عبيدات، محمود محمد سالم (جامعة الأزهر - كلية التربية, 2013)
تبحث هذه الورقة في علاقة الأنا بالآخر، إذ إن هذه العلاقة تدخل في إطار معين، تطرح من خلاله عنصر المواجهة والإبداع، بحيث تظهر الأنا من خلال المواجهة على حلبة الإبداع الأدبي ما دامت إشكالية الكتابة تلتصق بإشكالية الثقافة في المجتمعات، ولعله في هذا الجانب لا يتعارض الوعي الواقعي بأي وعي أخر. وبما أن الثقافة والأدب يرتبطان بحياة الشعوب بوعيهم للعالم، وبتأويلهم للكون، وبممارساتهم المتنوعة، فهما بذلك يرمزان إلى الثراء البشري، ويشيران إلى تنوع قدرات الناس الخلاقة. وعندما نتحدث عن فاعلية الآخر في الأدب العربي يجب علينا أن نلم بأسباب هذه الفاعلية بوسائلها ونتائجها، مع أن هذه الأسباب تختلف وتتغير بحسب الظروف والمعطيات. ولا يعني هذا التأثر أن الأدباء كانوا مقلدين للأدباء الغربيين، وإنما كان في أدبهم إبداع وأصالة، لأنهم استطاعوا أن يسخروا ما أفادوه من الثقافة الغربية في تطور أدبهم القومي من خلال الاهتمام بمعالجة قضايا المجتمعات العربية ومشكلاتها الاجتماعية.
The present paper investigates the cultural self-other relationship, as such relationship is conceptualized within a specific conceptual framework, in which struggle and creativity are most emphasized, where the self is delivered through struggling on the literary creativity stage, as long as problematic authoring closely relates to problematic culture of a community. In that context the consciousness to reality would not contradict with any other conscious. As culture and literature both associate with people lives, consciousness, word views, and their varied practices, they as a result, symbolize human enrichment, and indicate fertility of creative capabilities of people. When talking about effectiveness of the other m eyes of the Arabic literature, one, therefore, must address means, cause and effect of such effectiveness, though such causes may differ and vary by conditions and givens. Being impressed does not mean that Arab literates were mimic to their Western counterparts. On the contrary, Arab literate’ works are characterized by creativity and originality as Arab literates were capable to employ what they benefited from the Western culture in development of their national literature while dealing with issues and social problems of their own communities.
Keywords: ثقافة التغريب -- الإبداع الأدبى -- الثقافة المجتمعية -- الثقافة الغربية